Disease-free plant production and rapid propagation of some Cymbidium cultivars by meristem culture - Huyen, Phan Xuan; Ai, Nguyen Trung; Lang, Nguyen Thi; Dieu Huong, Nguyen Thi; Khiem, Dinh Van; Nhut, Duong Tan (Academia Journal of Biology, 2015)
In this paper, the protocol for disease-free plant production and rapid propagation of some Cymbidium cultivars by meristem culture are presented. Proliferation and multiplication rate of PLB were promoted in MS medium supplemented with 0.2 mg/l NAA and 2.0 mg/l BA. To increase the multiplication rate, PLB was cut in to 4 parts for subculture. This cutting way was better as compared to that of 2 parts. Shoots were well rooted on MS medium plus 0.5 mg/l NAA. 100% survival rate of Cymbidium plantlets was obtained after transferring to the greenhouse. This protocol can be applied for the micropropagation of many Cymbidium cultivars with great number and uniform plantlets.